2014
DOI: 10.1007/s11906-014-0499-8
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed for Hypertension: Implications for Blood Pressure Regulation

Abstract: Hypertension is the single largest risk factor attributed to mortality in the world. Medications are the primary treatment for hypertension; however, adherence to drug regimens is low (~50 %). Low adherence may be a contributing factor leading to uncontrolled blood pressure in patients. An effective alternative or complement to medications in managing hypertension is through lifestyle modifications. Adopting a healthy diet is a valuable strategy. A recent, randomized controlled year-long trial observed impress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…It has been shown in Sprague Dawley male rats that SDG reduced angiotensin I-induced increase of BP through stimulation of guanylate cyclase enzyme [36]. Another important component of flaxseed, ALA is the main component of flaxseed which reduce the values of BP, through its ability to reduce the activity of soluble epoxide hydrolase [7]. It has been shown that these pro-inflammatory oxylipins produced by soluble epoxide hydrolase are responsible for loss of vasodilatation and progression of inflammation in arterial hypertension [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown in Sprague Dawley male rats that SDG reduced angiotensin I-induced increase of BP through stimulation of guanylate cyclase enzyme [36]. Another important component of flaxseed, ALA is the main component of flaxseed which reduce the values of BP, through its ability to reduce the activity of soluble epoxide hydrolase [7]. It has been shown that these pro-inflammatory oxylipins produced by soluble epoxide hydrolase are responsible for loss of vasodilatation and progression of inflammation in arterial hypertension [7].…”
Section: Discussionmentioning
confidence: 99%
“…Another important component of flaxseed, ALA is the main component of flaxseed which reduce the values of BP, through its ability to reduce the activity of soluble epoxide hydrolase [7]. It has been shown that these pro-inflammatory oxylipins produced by soluble epoxide hydrolase are responsible for loss of vasodilatation and progression of inflammation in arterial hypertension [7]. However, a recent human study proved that flaxseed might reduce inflammation by decreasing the levels of neutrophil aggregating oxylipins [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability for n−3 fatty acids in flaxseed to reduce blood pressure has been clearly documented (Caligiuri, Edel, Aliani, and Pierce, 2014;Ueshima et al, 2007). Several studies in humans have demonstrated the ability of ALA or FXO to reduce diastolic blood pressure (DBP) (West et al, 2010), systolic blood pressure (SBP) (Djoussé et al, 2005) or both DBP and SBP (Paschos, Magkos, Panagiotakos, Votteas, and Zampelas, 2007;Rodriguez-Leyva et al, 2013;Takeuchi et al, 2007).…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Although outside of the CVD perspective, we note that dietary fiber from whole grains also appears to protect against colorectal cancer in another systematic review [31]. Linseed, as this is high in dietary fiber, lignans and n-3 polyunsaturated fatty acids (PUFA) and there is some evidence for CVD-related benefits as per three reviews [32][33][34] and a recent trial [35]. More specifically, two meta-analyses report blood pressure reduction associated with linseed consumption [21,22].…”
Section: Potential Ingredients Considered For Bread Designsmentioning
confidence: 97%